Atlas of Fundus Autofluorscence Imaging - Holz, Frank; Spaide, Richard; Bird, Alan C.; Schmitz-Valckenberg, Steffen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
During recent years, FAF (Fundus autofluorescence) imaging has been shown to be useful in various retinal diseases with regard to diagnostics, documentation of changes, identification of disease progression, and monitoring of novel therapies. Hereby, FAF imaging gives additional information above and beyond conventional imaging tools. This unique atlas provides a comprehensive and up-to-date overview of FAF imaging in retinal diseases. It also compares FAF findings with other imaging techniques such as fundus photograph, fluorescein- and ICG angiography as well as optical coherence tomography. General ophthalmologists as well as retina specialists will find this a very useful guide which illustrates typical FAF characteristics of various retinal diseases.
Methodology -- Lipofuscin of the Retinal Pigment Epithelium -- Origin of Fundus Autofluorescence -- Fundus Autofluorescence Imaging with the Confocal Scanning Laser Ophthalmoscope -- How To Obtain the Optimal Fundus Autofluorescence Image with the Confocal Scanning Laser Ophthalmoscope -- Autofluorescence Imaging with the Fundus Camera -- Macular Pigment Measurement$1 (BTheoretical Background -- Macular Pigment Measurement $1 (BClinical Applications -- Evaluation of Fundus Autofluorescence Images -- Clinical Application -- Macular and Retinal Dystrophies -- Discrete Lines of Increased Fundus Autofluorescence in Various Forms of Retinal Dystrophies -- Age-Related Macular Degeneration I$1 (BEarly Manifestation -- Age-Related Macular Degeneration II$1 (BGeographic Atrophy -- Age-Related Macular Degeneration III$1 (BPigment Epithelium Detachment -- Age-Related Macular Degeneration IV$1 (BChoroidal Neovascularization (CNV) -- Idiopathic Macular Telangiectasia -- Chorioretinal Inflammatory Disorders -- Autofluorescence from the Outer Retina and Subretinal Space -- Miscellaneous -- Perspectives in Imaging Technologies -- Perspectives in Imaging Technologies.s
Keywords: Medicine; Radiology; Ophthalmology; Medicine & Public Health; Ophthalmology; Imaging / Radiology; Electronic books